Baltic Journal of Psychology; Volume 4, Number 1 - University of Latvia. Department of Psychology; Miezīte, Solveiga; Raščevska, Malgožata (University of Latvia. Department of Psychology, 2003)
Contents Editorial ...5 REPORTS OF EMPIRICAL STUDIES Psychometric Properties of the Latvian and Russian Version of the State-Trait Anxiety Inventory (form Y) / Daina Skuskovnika... 7 International Personality Item Pool: A Scientific Collaboratory and It's Implication for Latvia / Liva Gabrane... 16 School Attitude, Parental and Teacher Support, and Student Depression in Latvia: a Mediator Model / Rachel Nobel, Solveiga Miezītis, Ieva Ranka... 22 THEORETICAL ARTICLES Development of the Science of Psychology in Latvia after the regaining of Independece (1992-2002) / Viesturs Renge... 34 Competence vs. Intelligence in Predicting Work Performance Uldis Pavuls... 53 RAKSTU KOPSAVILKUMI LATVIEŠU VALODĀ ...67 PROFESSIONAL ACADEMIC ISSUES IN PSYCHOLOGY IN BALTICS Psychologist Assistant's Professional Standards...74 Psihologa asistenta profesijas standarts... 80 Notes on Authors... 87
Baltijas Psiholoģijas Žurnāls
Keywords: Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology; Psiholoģija; Psihometrija; Personība; Intelekts; Izglītības psiholoģija; Personality; Intellect; Psychometrics; Educational psychology